Searching the essence of the Malaysian Constitution: between Islam and secular - Shuaib, Farid Sufian (2014)
This paper seeks to find the essence of the Malaysian constitution, between the Islamic and secular character of the constitution. The research examines the history and drafting of the constitution and studies the text of the Federal Constitution. The paper explores the meaning of secularism and secular state and compares the application of secular character in the constitution of some European countries. Several relevant case laws from Europe provide a comparative material in considering the extension of the same approach to Malaysia. The effect of such characterisation of a constitution and a country in the application of ordinary laws is considered.